2012
DOI: 10.1680/geot.12.og.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of gas-charged marine plastic sediments

Abstract: Understanding how free gas modifies the mechanical behaviour of marine plastic sediments remains a challenging issue. Special triaxial tests were carried out on natural sediments recovered from the Gulf of Guinea. Special attention was devoted to the laboratory preparation procedure, involving saturation of natural marine sediment samples with carbonated water and generation of free gas following undrained unloading. Experimental data show that soil destructuration and damage generated by gas expansion and exs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 19 publications
2
75
1
Order By: Relevance
“…Sultan et al (2012) noted that the presence of gas has a similar effect on the G u of natural Gulf of Guinea (GoG) clay samples. Other results of triaxial tests reported by Wheeler et al (1991) revealed that the normalised Young's modulus measured at an axial strain of 0 .…”
Section: Elastic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sultan et al (2012) noted that the presence of gas has a similar effect on the G u of natural Gulf of Guinea (GoG) clay samples. Other results of triaxial tests reported by Wheeler et al (1991) revealed that the normalised Young's modulus measured at an axial strain of 0 .…”
Section: Elastic Propertiesmentioning
confidence: 99%
“…85. The presence of gas bubbles can have significant effects on the consolidation behaviour and strength properties, with gassy soils reacting differently compared to saturated soils to environmental changes in load and temperature (Esrig & Kirby, 1977;Sills & Wheeler, 1992;Grozic et al, 1999;Sills & Gonzalez, 2001;Amaratunga & Grozic, 2009;Puzrin et al, 2011;Rebata-Landa & Santamarina, 2012;Sultan et al, 2012). Accordingly, gas-charging has important consequences for slope stability assessment, waste management and in turn for the planning of on-and offshore engineering operations Tjelta et al, 2007;Mabrouk & Rowe, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sultan et al (2012) carried out experiments on natural mudstone samples filled by gas-saturated water under confining pressure, recovered by coring from the continental slope of the Gulf of Guinea at about 20 m below seafloor. The experiment showed that lowering the confining pressure resulted in immediate decrease of P-and S-wave velocities.…”
Section: Role Of Gasmentioning
confidence: 99%
“…The papers by Sultan et al (2012) and Torisu et al (2012) tackle the intrinsic response of soil in two different scenarios. Sultan et al (2012) are concerned with the effect of gas, which frequently occurs at offshore development sites, on the behaviour of soil and particularly when the gas comes into or out of solution.…”
Section: Editorialmentioning
confidence: 99%
“…The papers by Sultan et al (2012) and Torisu et al (2012) tackle the intrinsic response of soil in two different scenarios. Sultan et al (2012) are concerned with the effect of gas, which frequently occurs at offshore development sites, on the behaviour of soil and particularly when the gas comes into or out of solution. Torisu et al (2012) are more concerned with rate effects on the response of deep marine clays, and present experimental results with loading rates spanning two orders of magnitude.…”
Section: Editorialmentioning
confidence: 99%